Photobiomodulation ameliorates inflammatory parameters in fibroblast-like synoviocytes and experimental animal models of rheumatoid arthritis - Ryu, Ji Hyeon; Park, Jisu; Kim, Bo-Young; Kim, Yeonye; Kim, Nam Gyun; Shin, Yong-Il (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is a chronic destructive inflammatory disease that afflicts over one percent of the world’s population. Current pharmacological treatments remain relatively ineffective. In this context, photobiomodulation (PBM) appears as a potential resource for the treatment of RA. This study was performed to investigate the anti-arthritic effects and related mechanisms of PBM on fibroblast-like synoviocytes (FLSs) from RA patients and a mouse model of collagen-induced arthritis (CIA). The RA-FLSs were irradiated with a light emitting diode (LED) at a wavelength of 610 nm for 20 min, and the corresponding power intensities were 5 and 10 mW/cm2. After the LED irradiation, cell viability, proliferation, migration, and invasion assays were performed. Male DBA/1J mice were used to establish an animal model of CIA. Light stimulation with 10 mW/cm2 was applied to the ankle joints via direct contact with the skin for 40 min, daily for 2 weeks. PBM significantly reduced tumor necrosis factor (TNF)-α-induced increase in proliferation, migration, and invasion in RA-FLSs. Moreover, PBM greatly inhibited the induction and development of CIA, resulting in the inhibition of synovial inflammation and cartilage degradation. PBM therapy decreased the serum levels of pro-inflammatory cytokines, while increasing the anti-inflammatory cytokines. PBM suppressed the translocation of nuclear factor-κappa B (NF-κB) and activation of NLRP3 inflammasome in the ankle joint. Furthermore, PBM showed a more pronounced anti-arthritic effect when combined with methotrexate (MTX), a disease-modifying anti-rheumatic drug (DMARD). The results showed that the effectiveness of MTX + PBM in CIA is superior to that of either MTX or PBM and that both work synergistically. Thus, PBM with LED could be used as a potential therapeutic intervention for RA.